Fatigue crack growth under non-proportional mixed-mode I + II. Role of compression while shearing. (May 2020) - Bonniot, Thomas; Doquet, Véronique; Mai, Si Hai
Highlights: Compression while shearing during sequential mode I + II extends coplanar growth. Compression changes the effective mode mixity, which rises during crack growth. Crack faces friction and wear control the crack paths and growth kinetics. Taking into account contact and friction stresses improves crack path predictions. The crack growth rates correlate well with a combination of effective ΔKI & ΔKII . Abstract: Mode I + II fatigue crack growth tests are run, following sequential or pseudo-sequential loading paths, representative of those computed for "squat type" cracks in rails. Stereo DIC provides the near-tip displacements, from which Δ K I effective and Δ K II effective are derived. Compression while shearing extends coplanar growth, by slowing down the wear-induced rise of the effective mode mixity ratio, up to the critical value for which bifurcation occurs. The consideration of plasticity and contact and friction stresses improves crack paths predictions, compared to the maximum tangential stress criterion. The coplanar crack growth rate correlates well with a combination of Δ K I effective and Δ K II effective .